Black Flag - Ricciardi, David (New York Berkley, 2021)
"After years of relative calm, piracy has returned to the high sea. But the days of AK-47s and outboard engines are over. The new pirates hit like a SEAL team. Highly trained and using cutting-edge technology, they make sure their victims are never heard from again. Ships and crews are vanishing at a staggering rate. As the threat to international shipping grows, United States authorities become determined to find the source of this new danger. Jake Keller has a plan-to lure the pirate mastermind out of hiding by infiltrating his organization-but it is a dangerous gambit, made more so by Jake's personal involvement with the beautiful heiress to a Greek shipping fortune and an ulterior agenda coming out of CIA headquarters. As the threats close in from all sides, Jake finds himself faced with a familiar choice: back off, or go on the offensive. His fate and the fate of a nation hang on his decision"--
112663
Keywords: Keller, Jake -- (Fictitious character) -- Fiction; United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; United States. -- Central Intelligence Agency; Intelligence officers -- United States -- Fiction; Piracy -- Fiction; Undercover operations -- Fiction; Heiresses -- Fiction; Employees; United States; Action and adventure fiction; Fiction; Spy fiction; Thrillers (Fiction)